Analysis of Unlawful Acts in the Installation of Electricity Poles on Private Land without the Consent of the Landowner - Tetuko Trie Wicaksana; Gusti Yosi Andri; Zelfi Ghaffar Aufiya (Ann Publisher, 2026)
Background. The research stems from a discrepancy between legal regulations regarding land use for the public interest and the practices observed on the ground. In some cases, the installation of electricity poles is still carried out without the consent of the landowner, even without adequate guarantees. This condition raises questions about whether such actions can be classified as unlawful. Aims. This research aims to examine these matters while analyzing how the conflict between public interests and individual rights is understood through Ronald Dworkin's perspective Methods. A juridical normative approach to examine laws and regulations, as well as a philosophical approach. Result. The outcome of this exploration also reveals that the installation of electricity poles without consent fulfills the elements of an unlawful act, starting from the existence of the action, the unlawful nature, error, loss, and a causal relationship. Conclusion. In Dworkin's framework, individual rights cannot simply be overridden by the public interest, especially if accompanied by a clear legal basis and fair compensation.